Method for constructing flame-retardant super-hydrophobic self-cleaning coating on wood surface

By constructing a flame-retardant superhydrophobic self-cleaning coating on the surface of the wood, using the DOPO-SiO2 micro-nano hydrophobic structure and the low surface energy of PDMS, combined with the flame retardant effect of APP, the problems of toxic halogen flame retardant, low production efficiency, and flame retardant outflow in the existing wood flame retardant technology are solved, and the superhydrophobic self-cleaning effect of the wood surface is achieved and the flame retardant performance of the wood is improved.

CN119708949AActive Publication Date: 2025-03-28YIWU HUAHONG CULTURE CREATIVE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411777697.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-28
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing wood flame retardant technology has problems such as toxic halogen flame retardant, low production efficiency, and degradation of wood flame retardant performance due to flame retardant outflow, which is difficult to meet the requirements of modern industry for environmental protection and health.

Method used

By constructing a flame-retardant superhydrophobic self-cleaning coating on the surface of the wood, a coating with superhydrophobic self-cleaning effect is formed by using the "semi-inlaid" DOPO-SiO2 micro-nano hydrophobic structure and the low surface energy of PDMS, combined with the flame-retardant effect of APP.

Benefits of technology

The superhydrophobic self-cleaning effect of wood surface is achieved and the flame retardant performance of wood is improved, the loss of flame retardant is reduced, and the tolerance to the water environment is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708949A_ABST
    Figure CN119708949A_ABST
Patent Text Reader

Abstract

The invention relates to the field of coatings, and discloses a method for constructing a flame-retardant super-hydrophobic self-cleaning coating on the surface of wood, which comprises the following steps: 1) modifying the surface of the wood by using KH550 to obtain the wood with positive electricity on the surface; (2) ammonium polyphosphate is adsorbed to the surface of the wood through the electrostatic interaction, and an APP / KH550 electrostatic composite layer is formed; (3) DOPO-SiO2 is prepared; and (4) DOPO-SiO2, PDMS, epoxy resin and a curing agent are prepared into paint, the paint is sprayed to the surface of the wood, and the flame-retardant super-hydrophobic self-cleaning coating is formed through curing. By means of the method, the flame-retardant super-hydrophobic self-cleaning coating can be constructed on the wood surface, the surface of the coating is provided with a micro-nano hydrophobic structure composed of DOPO-SiO2 in a semi-inlaid state, and the surface of the coating has the super-hydrophobic self-cleaning effect in combination with low surface energy of PDMS; and meanwhile, DOPO in the outer layer of the coating and APP in the inner layer of the coating have a synergistic flame retardant effect, and the flame retardance of the wood can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, and in particular to a method for constructing a flame-retardant super-hydrophobic self-cleaning coating on a wood surface. Background Art

[0002] Wood is one of the oldest materials. It is often used in construction, furniture and decoration because of its light weight, high strength-to-weight ratio, good texture, thermal insulation and electrical insulation properties. However, wood is flammable, which limits its application to a certain extent. Physical penetration is a traditional flame retardant treatment method to impregnate halogen flame retardants into the pores of wood. However, halogen flame retardants release toxic and corrosive gases during combustion, which are harmful to the environment and human health, and cannot meet the environmental and health requirements of modern industry. At present, wood flame retardancy mainly relies on applying chemical synthetic flame retardants to wood by vacuum pressure impregnation. The process includes vacuuming, pressurizing and maintaining pressure. The process is relatively complicated and the production efficiency is low. Although impregnation under normal pressure is low-cost, it will result in the flame retardant not penetrating deeply into the wood. Therefore, the development of efficient and sustainable wood flame retardant coatings is the focus of current wood flame retardant research.

[0003] In practical applications, the degradation of wood flame retardancy is inevitable due to the inherent hygroscopicity of wood and the resulting outflow of flame retardants. Most coatings are easily affected by dirt, moisture and water, resulting in the destruction of wood flame retardancy and low tolerance to water environments. Therefore, there is an urgent need to develop durable flame retardant coatings with water-repellent and self-cleaning properties for natural wood materials. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for constructing a flame-retardant super-hydrophobic self-cleaning coating on the surface of wood. The flame-retardant super-hydrophobic self-cleaning coating can be constructed on the surface of wood by the method of the present invention. The surface of the coating has a micro-nano hydrophobic structure composed of DOPO-SiO2 in a "semi-mosaic" state, combined with the low surface energy of PDMS, so that the surface of the coating has a super-hydrophobic self-cleaning effect; at the same time, because the outer layer of the coating also contains DOPO, it has a synergistic flame retardant effect with the inner layer of APP, which can further improve the flame retardancy of the wood.

[0005] The specific technical solution of the present invention is: a method for constructing a flame-retardant super-hydrophobic self-cleaning coating on a wood surface, specifically comprising the following steps: 1) Immerse the wood in an alkaline solution, add KH550 ethanol solution, and heat to react to obtain wood with a positively charged surface.

[0006] In step 1), KH550 is hydrolyzed to generate silanol bonds, which undergo hydrolysis and polycondensation reactions with the hydroxyl groups on the wood surface. The modified wood surface contains positively charged amino groups.

[0007] 2) Immerse the wood in ammonium polyphosphate solution and heat it to form an APP / KH550 electrostatic composite layer on the wood surface.

[0008] 3) Add KH570 ethanol solution to nano-SiO2 alkaline solution and heat to react; add DOPO ethanol solution and heat to react to obtain DOPO-SiO2.

[0009] In step 3), KH570 is hydrolyzed to generate silanol bonds, which undergo hydrolysis and polycondensation reactions with the hydroxyl groups on the surface of nano-SiO2. The modified surface of nano-SiO2 contains double bonds, which undergo addition reactions with the PH bonds of DOPO.

[0010] 4) Mixing the dispersion containing DOPO-SiO2 with the mixed solution containing PDMS and epoxy resin, adding epoxy resin curing agent and PDMS curing agent to obtain a coating; spraying the coating on the surface of the wood obtained in 2), and forming a flame-retardant, super-hydrophobic and self-cleaning coating on the surface of the wood after curing.

[0011] In the above preparation process, the present invention first grafts γ-aminopropyltriethoxysilane (KH550) on the wood to make the wood surface positively charged, and then the negatively charged ammonium polyphosphate (APP) is adsorbed on the surface of KH550 through electrostatic action, thereby forming an APP / KH550 electrostatic composite layer on the wood surface. This method can significantly increase the loading rate of APP on the wood surface during the impregnation process. On the other hand, γ-methacryloxypropyltrimethoxysilane (KH570) is used to modify the surface of nano-SiO2, creating conditions for the subsequent grafting of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) flame retardant, and finally obtaining DOPO-SiO2 (the core is nano-SiO2, and its surface is coated with a layer of DOPO). Finally, polydimethylsiloxane (PDMS) and epoxy resin were used as coating film-forming materials and mixed with DOPO-SiO2 to prepare a coating, which was sprayed on the wood surface with an APP / KH550 electrostatic composite layer to form a flame-retardant super-hydrophobic self-cleaning coating. In the above coating, the inner layer is an APP / KH550 electrostatic composite layer, and APP can give the wood a flame-retardant effect; the outer layer matrix is ​​a cured PDMS and epoxy resin, and DOPO-SiO2 is adhered to the surface of the matrix. These DOPO-SiO2 are attached to the surface of the outer layer matrix in a "semi-embedded" manner (that is, the bottom of the particles are embedded in the matrix, and the top is exposed to the surface of the matrix), thereby constructing a micro-nano surface structure with a hydrophobic effect (the nanoscale surface structure is formed by dispersed DOPO-SiO2, and the micron-scale surface structure is formed by partially agglomerated DOPO-SiO2). On this basis, the low surface energy provided by PDMS is further combined to make the outer coating have a super-hydrophobic self-cleaning effect (contact angle>150°, rolling angle<10°). At the same time, since the outer layer also contains DOPO, it has a synergistic flame retardant effect with APP, which can further improve the flame retardancy of the wood.

[0012] Preferably, in step 3), the usage ratio of nano-SiO2, KH570 and DOPO is (2.5-3.5 g): (1-2 mL): (3.5-4.5 g).

[0013] Preferably, in step 4), the mass ratio of DOPO-SiO2, epoxy resin and PDMS in the coating is (1-2): (0.5-2): (0.5-2).

[0014] The present invention finds that the amount of epoxy resin and PDMS relative to DOPO-SiO2 in the coating is crucial to whether a micro-nano surface structure can be formed. The appropriate amount of epoxy resin and PDMS can not only firmly fix DOPO-SiO2, but also ensure that most of DOPO-SiO2 is in a "semi-embedded" state. If the amount of epoxy resin and PDMS is too small, DOPO-SiO2 cannot be effectively fixed; on the contrary, if the content is too much, the formed coating will completely cover DOPO-SiO2, so that the coating surface does not have a micro-nano hydrophobic structure.

[0015] Preferably, in step 1), the wood is basswood.

[0016] Preferably, in step 1), the wood is subjected to surface roughening pretreatment. More preferably, the surface roughening pretreatment is sanding the wood surface with sandpaper, ultrasonic cleaning, and drying. More preferably, the sandpaper has a mesh size of 350-450.

[0017] Preferably, in step 1), the volume ratio of KH550 to ethanol in the KH550 ethanol solution is (5-7): (36-43).

[0018] Preferably, in step 1), the heating reaction temperature is 35-45° C. and the time is 2-2.5 h.

[0019] Preferably, in step 2), the content of ammonium polyphosphate in the ammonium polyphosphate solution is 8-12 g / 100 mL.

[0020] Preferably, in step 2), the heating temperature is 45-55° C. and the heating time is 2-2.5 h.

[0021] Preferably, in step 3), the particle size of the nano-SiO2 is 300-600nm.

[0022] Preferably, in step 3), the temperature of the first heating reaction is 35-40°C and the time is 25-35 min; the temperature of the second heating reaction is 85-95°C and the time is 3.5-4.5 h.

[0023] Preferably, in step 4), the solvent of the dispersion and the mixed solution is ethyl acetate.

[0024] Preferably, in step 4), the curing agent includes epoxy resin curing agent and PDMS curing agent.

[0025] Preferably, in step 4), the curing temperature is 80-90° C. and the curing time is 2-3 hours.

[0026] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention first grafts KH550 onto wood to make the wood surface positively charged, and then the negatively charged APP is adsorbed on the surface of KH550 through electrostatic action, thereby forming an APP / KH550 electrostatic composite layer on the wood surface. This method can significantly increase the loading rate of APP on the wood surface during the impregnation process.

[0027] (2) The coating surface has a micro-nano hydrophobic surface structure composed of "semi-inlaid" DOPO-SiO2, which, combined with the low surface energy provided by PDMS, makes the coating surface have a super-hydrophobic self-cleaning effect (contact angle > 150°, rolling angle < 10°). At the same time, since the outer layer of the coating also contains DOPO, it has a synergistic flame retardant effect with APP, which can further improve the flame retardancy of wood. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the synthesis of DOPO-SiO2 of the present invention.

[0029] Figure 2 This is an electron microscope image of the nano-SiO2 obtained in Example 1 with a magnification of 20,000 times.

[0030] Figure 3 This is an electron microscope image of DOPO-SiO2 obtained in Example 1 at a magnification of 20,000 times.

[0031] Figure 4 This is an electron microscope image of the log at a magnification of 500 times.

[0032] Figure 5 This is an electron microscope image of the APP modified wood obtained in Example 1 at a magnification of 500 times.

[0033] Figure 6 This is an electron microscope image of the flame-retardant super-hydrophobic self-cleaning coating on the wood surface obtained in Example 1 at a magnification of 1000 times.

[0034] Figure 7 This is an electron microscope image of the wood surface coating obtained in Comparative Example 1 at a magnification of 1000 times.

[0035] Figure 8 This is a contact angle picture of the wood surface treated in Example 1.

[0036] Fig. 9 FT-IR spectra of nano-SiO2, K570 modified SiO2 and DOPO-SiO2 obtained in Example 1.

[0037] Fig.10 These are digital pictures of the burning of logs, Example 1, Comparative Example 3 and Comparative Example 4.

[0038] Fig.11These are digital images of logs (a), Example 1 (b), Comparative Example 3 (c) and Comparative Example 4 (d) after combustion.

[0039] Fig.12 The self-cleaning performance diagram of the original wood (ad) and Example 1 (eh).

[0040] Fig.13 The digital pictures of Comparative Example 3 (a) and Example 1 (b) are soaked in water, and the digital pictures of Comparative Example 3 (c) and Example 1 (d) are burned after soaking. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with the embodiments.

[0042] A method for constructing a flame-retardant super-hydrophobic self-cleaning coating on a wood surface, which specifically comprises the following steps: 1) Immerse the wood in an alkaline solution, add KH550 ethanol solution, heat and react, and obtain wood with a positive charge on the surface after the reaction.

[0043] In some specific implementation cases, the wood is basswood, and its size is 5 cm×2.5 cm×0.15 cm.

[0044] In some specific implementation cases, the wood is subjected to surface roughening pretreatment; in some more specific implementation cases, the surface roughening pretreatment is specifically polishing the wood surface with 350-450 mesh sandpaper, washing with deionized water and ethanol under ultrasonic conditions for 2-10 minutes each, drying at 60-70°C, and setting aside.

[0045] In some specific implementation cases, the volume ratio of KH550 to ethanol in the KH550 ethanol solution is (5-7): (36-43).

[0046] In some specific implementation cases, the alkaline solution is composed of aqueous ammonia (concentration 25-28%) and water in a volume ratio of (8-12):(45-55).

[0047] In some specific implementation cases, the temperature of the heating reaction is 35-45° C., and the heating reaction time is 2-2.5 h.

[0048] 2) Immerse the wood in ammonium polyphosphate solution and heat it to form an APP / KH550 electrostatic composite layer on the wood surface through electrostatic adsorption.

[0049] In some specific implementation cases, the content of ammonium polyphosphate in the ammonium polyphosphate solution is 8-12 g / 100 mL.

[0050] In some specific implementation cases, the heating treatment temperature is 45-55° C., and the heating treatment time is 2-2.5 h.

[0051] 3) Add KH570 ethanol solution to nano-SiO2 alkaline solution for heating reaction; add DOPO ethanol solution for further heating reaction to obtain DOPO-SiO2 (the reaction principle is as follows Figure 1 as shown).

[0052] In some specific implementation cases, the particle size of the nano-SiO2 is 300-600nm.

[0053] In some specific implementation cases, the nano-SiO2 alkaline solution is composed of nano-SiO2, ammonia water (concentration 25-28%) and water.

[0054] In some specific implementation cases, the usage ratio of nano-SiO2, water, ammonia water, KH570, DOPO and ethanol is (2.5-3.5 g): (45-55 mL): (8-12 mL): (1-2 mL): (3.5-4.5 g): (450-550 mL).

[0055] In some specific implementation cases, the temperature of the first heating reaction is 35-40°C, and the heating reaction time is 25-35 minutes; the temperature of the second heating reaction is 85-95°C, and the heating reaction time is 3.5-4.5 hours.

[0056] 4) Mixing the dispersion containing DOPO-SiO2 with the mixed solution containing PDMS and epoxy resin, adding epoxy resin curing agent and PDMS curing agent to obtain a coating; spraying the coating on the surface of the wood having the APP / KH550 electrostatic composite layer obtained in 2) to form a flame retardant, super hydrophobic and self-cleaning coating on the wood surface after curing.

[0057] In some specific implementation cases, the solvent of the dispersion and the mixed solution is ethyl acetate.

[0058] In some specific implementation cases, the dosage ratio of DOPO-SiO2, epoxy resin, PDMS and ethyl acetate in the coating is (1-2 g): (0.5-2 g): (0.5-2 g): (20-30 mL).

[0059] In some specific implementation cases, the curing agent includes an epoxy resin curing agent and a PDMS curing agent.

[0060] In some specific implementation cases, the curing temperature is 80-90° C. and the curing time is 2-3 hours.

[0061] In some specific implementation cases, the contact angle of the flame-retardant super-hydrophobic self-cleaning coating is greater than 150°, and the rolling angle is less than 10°.

[0062] Specific Examples and Comparative Examples Example 1 (1) The surface of wood chips (basswood, size 5 cm × 2.5 cm × 0.15 cm) was polished with 400-grit sandpaper, washed with deionized water and ethanol under ultrasonic conditions for 5 min each, and dried at 60 °C to obtain surface roughened pretreated wood chips.

[0063] (2) Add 50 mL of deionized water and 10 mL of ammonia water (concentration of 27%) into a beaker, stir at 450 rpm for 30 min at 35 °C to form an alkaline solution, put the wood chips pretreated with surface roughening into the beaker, prepare a modification solution containing 6 mL of KH550 and 40 mL of ethanol, add the modification solution dropwise into the beaker, stir at 450 rpm for 2 h at 40 °C, wash with ethanol three times after the reaction is completed, and dry at 60 °C for 10 min to obtain KH550-modified wood chips.

[0064] (3) Add 100 mL of deionized water and 10 g of APP into a beaker, stir at 50°C at 400 rpm until dissolved, then add the KH550-modified wood chips obtained in step (2) into the beaker, continue stirring at 50°C at 400 rpm for 2 h, wash with ethanol three times after the reaction is completed, and dry at 80°C for 12 h to obtain wood chips with an APP / KH550 electrostatic composite layer on the surface, which are set aside.

[0065] (4) Add 200 mL of ethanol, 50 mL of deionized water, and 20 mL of ammonia water (concentration of 27%) into a beaker, stir at 600 rpm, then add 8 mL of ethyl orthosilicate, and continue stirring at 600 rpm for 4 h. After the reaction is completed, wash with deionized water and ethanol three times respectively, and dry at 60 °C for 24 h to obtain nano-SiO2.

[0066] (5) Add 3g of nano-SiO2 obtained in step (4), 50mL of deionized water, and 10mL of ammonia water (concentration of 27%) to a three-necked flask, stir at 35°C at 450rpm for 30min to form an alkaline solution, prepare a modified solution containing 1.5mL of KH570 and 40mL of ethanol, drop the modified solution into the three-necked flask, and stir at 40°C at 450rpm for 2h. Prepare a modified solution of 4g of DOPO and 100mL of ethanol, add the modified solution into the three-necked flask, stir at 90°C at 450rpm for 4h, add 50mL of ethanol every 0.5h, wash with deionized water and ethanol three times respectively after the reaction is completed, and dry at 60°C for 24h to obtain DOPO-SiO2.

[0067] (6) Add 1.5 g of DOPO-SiO2 obtained in step (5) into 10 mL of ethyl acetate solution and ultrasonically disperse for 30 min to obtain dispersion A. Add 1 g of epoxy resin and 1 g of PDMS into 15 mL of ethyl acetate solution and stir at 400 rpm for 30 min to obtain dispersion B. Then add dispersion A into dispersion B and stir at 400 rpm for 30 min. Add 0.2 g of epoxy resin curing agent and 0.1 g of PDMS curing agent and continue stirring for 15 min. Finally, spray the mixture onto the surface of the wood chip having the APP / KH550 electrostatic composite layer obtained in step (3). After curing at 80° C. for 2 h, a wood chip having a flame retardant, super hydrophobic and self-cleaning coating on the surface is obtained.

[0068] Comparative Example 1 (1) The surface of wood chips (basswood, size 5 cm × 2.5 cm × 0.15 cm) was polished with 400-grit sandpaper, washed with deionized water and ethanol under ultrasonic conditions for 5 min each, and dried at 60 °C to obtain surface roughened pretreated wood chips.

[0069] (2) Add 50 mL of deionized water and 10 mL of ammonia water (concentration of 27%) into a beaker, stir at 450 rpm for 30 min at 35 °C to form an alkaline solution, put the wood chips pretreated with surface roughening into the beaker, prepare a modification solution containing 6 mL of KH550 and 40 mL of ethanol, add the modification solution dropwise into the beaker, stir at 450 rpm for 2 h at 40 °C, wash with ethanol three times after the reaction is completed, and dry at 60 °C for 10 min to obtain KH550-modified wood chips.

[0070] (3) Add 100 mL of deionized water and 10 g of APP into a beaker, stir at 50°C at 400 rpm until dissolved, then add the KH550-modified wood chips obtained in step (2) into the beaker, continue stirring at 50°C at 400 rpm for 2 h, wash with ethanol three times after the reaction is completed, and dry at 80°C for 12 h to obtain wood chips with an APP / KH550 electrostatic composite layer on the surface, which are set aside.

[0071] (4) Add 200 mL of ethanol, 50 mL of deionized water, and 20 mL of ammonia water (concentration of 27%) into a beaker, stir at 600 rpm, then add 8 mL of ethyl orthosilicate, and continue stirring at 600 rpm for 4 h. After the reaction is completed, wash with deionized water and ethanol three times respectively, and dry at 60 °C for 24 h to obtain nano-SiO2.

[0072] (5) Add 3g of nano-SiO2 obtained in step (4), 50mL of deionized water, and 10mL of ammonia water (concentration of 27%) to a three-necked flask, stir at 35°C at 450rpm for 30min to form an alkaline solution, prepare a modified solution containing 1.5mL of KH570 and 40mL of ethanol, drop the modified solution into the three-necked flask, and stir at 40°C at 450rpm for 2h. Prepare a modified solution of 4g of DOPO and 100mL of ethanol, add the modified solution into the three-necked flask, stir at 90°C at 450rpm for 4h, add 50mL of ethanol every 0.5h, wash with deionized water and ethanol three times respectively after the reaction is completed, and dry at 60°C for 24h to obtain DOPO-SiO2.

[0073] (6) 1.5 g of DOPO-SiO2 obtained in step (5) was added to 10 mL of ethyl acetate solution and ultrasonically dispersed for 30 min to obtain dispersion A. 3 g of epoxy resin and 1 g of PDMS were added to 15 mL of ethyl acetate solution and stirred at 400 rpm for 30 min to obtain dispersion B. Dispersion A was then added to dispersion B and stirred at 400 rpm for 30 min. 0.6 g of epoxy resin curing agent and 0.1 g of PDMS curing agent were added and stirred for 15 min. Finally, the mixture was sprayed onto the surface of the wood chip having the APP / KH550 electrostatic composite layer obtained in step (3). After curing at 80° C. for 2 h, a wood chip having a flame retardant, super hydrophobic and self-cleaning coating on the surface was obtained.

[0074] Comparative Example 2 (1) The surface of wood chips (basswood, size 5 cm × 2.5 cm × 0.15 cm) was polished with 400-grit sandpaper, washed with deionized water and ethanol under ultrasonic conditions for 5 min each, and dried at 60 °C to obtain surface roughened pretreated wood chips.

[0075] (2) Add 50 mL of deionized water and 10 mL of ammonia water (concentration of 27%) into a beaker, stir at 450 rpm for 30 min at 35 °C to form an alkaline solution, put the wood chips pretreated with surface roughening into the beaker, prepare a modification solution containing 6 mL of KH550 and 40 mL of ethanol, add the modification solution dropwise into the beaker, stir at 450 rpm for 2 h at 40 °C, wash with ethanol three times after the reaction is completed, and dry at 60 °C for 10 min to obtain KH550-modified wood chips.

[0076] (3) Add 100 mL of deionized water and 10 g of APP into a beaker, stir at 50°C at 400 rpm until dissolved, then add the KH550-modified wood chips obtained in step (2) into the beaker, continue stirring at 50°C at 400 rpm for 2 h, wash with ethanol three times after the reaction is completed, and dry at 80°C for 12 h to obtain wood chips with an APP / KH550 electrostatic composite layer on the surface, which are set aside.

[0077] (4) Add 200 mL of ethanol, 50 mL of deionized water, and 20 mL of ammonia water (concentration of 27%) into a beaker, stir at 600 rpm, then add 8 mL of ethyl orthosilicate, and continue stirring at 600 rpm for 4 h. After the reaction is completed, wash with deionized water and ethanol three times respectively, and dry at 60 °C for 24 h to obtain nano-SiO2.

[0078] (5) Add 3g of nano-SiO2 obtained in step (4), 50mL of deionized water, and 10mL of ammonia water (concentration of 27%) to a three-necked flask, stir at 35°C at 450rpm for 30min to form an alkaline solution, prepare a modified solution containing 1.5mL of KH570 and 40mL of ethanol, drop the modified solution into the three-necked flask, and stir at 40°C at 450rpm for 2h. Prepare a modified solution of 4g of DOPO and 100mL of ethanol, add the modified solution into the three-necked flask, stir at 90°C at 450rpm for 4h, add 50mL of ethanol every 0.5h, wash with deionized water and ethanol three times respectively after the reaction is completed, and dry at 60°C for 24h to obtain DOPO-SiO2.

[0079] (6) Add 1.5 g of DOPO-SiO2 obtained in step (5) into 10 mL of ethyl acetate solution and ultrasonically disperse for 30 min to obtain dispersion A. Add 1 g of PDMS into 15 mL of ethyl acetate solution and stir at 400 rpm for 30 min to obtain dispersion B. Then add dispersion A into dispersion B and stir at 400 rpm for 30 min. Add 0.1 g of PDMS curing agent and continue stirring for 15 min. Finally, spray the mixture onto the surface of the wood chip having the APP / KH550 electrostatic composite layer obtained in step (3). After curing at 80° C. for 2 h, a wood chip having a flame retardant, super hydrophobic and self-cleaning coating on the surface is obtained.

[0080] Comparative Example 3 (1) The surface of wood chips (basswood, size 5 cm × 2.5 cm × 0.15 cm) was polished with 400-grit sandpaper, washed with deionized water and ethanol under ultrasonic conditions for 5 min each, and dried at 60 °C to obtain surface roughened pretreated wood chips.

[0081] (2) Add 50 mL of deionized water and 10 mL of ammonia water (concentration of 27%) into a beaker, stir at 450 rpm for 30 min at 35 °C to form an alkaline solution, put the wood chips pretreated with surface roughening into the beaker, prepare a modification solution containing 6 mL of KH550 and 40 ml of ethanol, add the modification solution dropwise into the beaker, stir at 450 rpm for 2 h at 40 °C, wash with ethanol three times after the reaction is completed, and dry at 60 °C for 10 min to obtain KH550-modified wood chips.

[0082] (3) Add 100 mL of deionized water and 10 g of APP into a beaker, stir at 50°C at 400 rpm until dissolved, then add the KH550-modified wood chips obtained in step (2) into the beaker, continue stirring at 50°C at 400 rpm for 2 h, wash with ethanol three times after the reaction is completed, and dry at 80°C for 12 h to obtain wood chips with an APP / KH550 electrostatic composite layer on the surface.

[0083] Comparative Example 4 (1) The surface of the wood chip (basswood) was polished with 400-mesh sandpaper, washed with deionized water and ethanol under ultrasonic conditions for 5 min each, and dried at 60°C to obtain a surface roughened pretreated wood chip.

[0084] (2) Add 100 mL of deionized water and 10 g of APP into a beaker and stir at 400 rpm at 50 °C until dissolved. Then, place the wood chips pretreated with surface roughening into the beaker and stir at 400 rpm at 50 °C for 2 h. After the reaction is completed, wash with ethanol three times and dry at 80 °C for 12 h to obtain APP-modified wood chips.

[0085] Performance Testing and Characterization Figure 2 This is an electron microscope image of the nano-SiO2 obtained in Example 1 with a magnification of 20,000 times. It can be seen that the nano-SiO2 is a regular sphere with an average particle size of 458nm. Figure 4 This is an electron microscope image of DOPO-SiO2 obtained in Example 1 at a magnification of 20,000 times. It can be seen that an irregular layer of DOPO is wrapped on the surface of the nano-SiO2.

[0086] Figure 4 This is an electron microscope picture of the log at a magnification of 500 times. The surface of the log is clearly fibrous and relatively smooth. Figure 5 This is an electron microscope image of the APP-modified wood obtained in Example 1 at a magnification of 500 times. Compared with the original wood, the surface of the APP-modified wood becomes slightly rough, which is mainly due to the adhesion of APP and APP / KH550 to the wood surface. Figure 6This is an electron microscope image of the flame-retardant super-hydrophobic self-cleaning coating on the wood surface obtained in Example 1 at a magnification of 1000 times. Due to the coverage of DOPO-SiO2 / PDMS / EP, the roughness of the wood surface is significantly increased, and micron- and nano-scale protrusions appear. Figure 7 The electron microscope image of the wood surface coating obtained in Comparative Example 1 at a magnification of 1000 times is shown. The difference between Comparative Example 1 and Example 1 is that 3g of epoxy resin is used. It is found that the addition of excessive epoxy resin wraps the DOPO-SiO2 nanoparticles, and the coating surface is blocky, and the super-hydrophobic effect is not achieved. The difference between Comparative Example 2 and Example 1 is that epoxy resin is not introduced. It is found that although Comparative Example 2 achieves a super-hydrophobic effect, the coating will fall off during the combustion process when using a single PDMS as a bonding layer. Figure 8 The contact angle picture of Example 1 shows that the contact angle of Example 1 is 151.2° and the rolling angle is 5.6°, achieving a super hydrophobic effect. The above results show that the content of epoxy resin in the coating affects the hydrophobicity of the coating and the adhesion of the coating on the substrate. Therefore, as described above, the performance of Example 1 is the best.

[0087] Fig. 9 The FT-IR spectra of nano-SiO2, K570-modified SiO2, and DOPO-SiO2 obtained in Example 1. In the FT-IR spectrum of SiO2, the absorption peak is at 1103 cm -1 The absorption peak is at 804 cm -1 and 470cm -1 is due to the symmetric stretching and bending vibrations of Si-O, with a wavelength of 940 cm -1 The absorption at 2958 and 2893 cm is the bending vibration of Si-OH. -1 The peak of -CH3 asymmetric stretching vibration is 3436cm -1 The -OH stretching vibration peak is at 1721 cm -1 The vibration peak of -C=O of silane coupling agent is 1637 cm -1 It is the characteristic peak of C=C. In the FT-IR spectrum of DOPO-SiO2, the disappearance of the characteristic peak of C=C can be explained by the reaction between the PH bond of DOPO and C=C.

[0088] Fig.10The burning digital pictures of logs, Example 1, Comparative Example 3 and Comparative Example 4. The log is removed after being placed on the flame of an alcohol lamp for 10s, and the log continues to burn violently until it is completely burned out. The APP / KH550 impregnated wood in Comparative Example 3 and the flame retardant super hydrophobic self-cleaning coating wood in Example 1 are removed after being placed on the flame of an alcohol lamp for 10s, and neither of them burns. Both are removed after being placed on the flame again for 10s, and flames appear on the wood chips and the flame spread speed is very slow. The flame on the APP / KH550 impregnated wood extinguishes itself when removed 6s, and the flame on the flame retardant super hydrophobic self-cleaning coating wood extinguishes itself when removed 7s. The wood directly impregnated with APP in Comparative Example 4 is removed after 10s on the flame of an alcohol lamp, and extinguishes itself after continuous burning for 18s, and is removed after being placed on the flame again for 10s, and the wood burns completely extinguished after 20s.

[0089] Fig.11 These are digital images of logs (a), Example 1 (b), Comparative Example 3 (c) and Comparative Example 4 (d) after combustion. Fig.11 (a) The burning logs form broken ash. Fig.11 (b) and Fig.11 (c) shows that the degree of damage to APP / KH550 impregnated wood after burning is deeper than that to flame retardant superhydrophobic self-cleaning coated wood after burning. Fig.11 (d) No ash falls after the wood directly impregnated with APP burns. The above results show that APP has a flame retardant effect on wood. The electrostatic effect of KH550 increases the loading amount of APP on the wood surface, so the flame retardant effect of APP / KH550 impregnated wood is much better than that of wood directly impregnated with APP, and the addition of DOPO-SiO2 has a synergistic effect on the flame retardancy of wood. The above results show that Example 1 has the best flame retardant effect.

[0090] Fig.12 The self-cleaning performance diagram of the original wood (ad) and Example 1 (eh). Fig.12 (ad) By dripping water droplets, the soil on the logs is not completely removed, and the wood surface is wetted by the water droplets, and the liquid containing the soil sticks to the surface, causing the surface to become dirtier. Fig.12 (df) The soil on the surface of the wood coating was taken away by dropping water droplets, indicating that the coating has extremely low adhesion to water and has excellent self-cleaning properties.

[0091] Fig.13 The digital pictures of Comparative Example 3 (a) and Example 1 (b) are soaked in water, and the digital pictures of Comparative Example 3 (c) and Example 1 (d) are burned after soaking. Fig.13 (a) shows that the APP / KH550 impregnated wood can still see clear wood texture when immersed in water. Fig.13(b) shows that a bright silver mirror appears on the coating surface because the air captured by the micro-nanostructure produces total reflection of light. APP / KH550 impregnated wood and Example 1 were immersed in water for 2 hours and then placed on an alcohol lamp to burn for 10 seconds before being removed. Fig.13 (c) shows that the APP / KH550 impregnated wood continued to burn vigorously until it was completely burned out. Fig.13 (d) shows that the wood with the flame retardant super hydrophobic self-cleaning coating in Example 1 self-extinguishes after burning for 10 seconds, and still has excellent flame retardant properties. The above results show that the flame retardant super hydrophobic self-cleaning coating in Example 1 effectively reduces the loss of wood flame retardant.

[0092] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0093] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for constructing a flame retardant super hydrophobic self-cleaning coating on a wood surface, characterized in that include: 1) Immerse the wood in an alkaline solution, add KH550 ethanol solution, and heat to react to obtain wood with a positively charged surface; 2) Immerse the wood in an ammonium polyphosphate solution and heat it to form an APP / KH550 electrostatic composite layer on the wood surface; 3) Add KH570 ethanol solution to nano-SiO2 alkaline solution and heat to react; add DOPO ethanol solution and heat to react to obtain DOPO-SiO2; the dosage ratio of nano-SiO2, KH570 and DOPO is (2.5-3.5g): (1-2mL): (3.5-4.5g); 4) Mixing a dispersion containing DOPO-SiO2 with a mixed solution containing PDMS and epoxy resin, and adding a curing agent; spraying the obtained coating on the surface of wood, and forming a flame-retardant, super-hydrophobic and self-cleaning coating after curing; the mass ratio of DOPO-SiO2, epoxy resin and PDMS is (1-2): (0.5-2): (0.5-2).

2. The method according to claim 1, characterized in that: In step 1), The wood is basswood; The wood is pre-treated to roughen its surface.

3. The method according to claim 1, characterized in that: In step 1), the volume ratio of KH550 to ethanol in the KH550 ethanol solution is (5-7): (36-43).

4. The method according to claim 1, characterized in that: In step 1), the heating reaction temperature is 35-45° C. and the time is 2-2.5 hours.

5. The method according to claim 1, characterized in that: In step 2), the content of ammonium polyphosphate in the ammonium polyphosphate solution is 8-12 g / 100 mL.

6. The method according to claim 1, characterized in that: In step 2), the heating temperature is 45-55° C. and the heating time is 2-2.5 h.

7. The method according to claim 1, characterized in that: In step 3), The particle size of the nano-SiO2 is 300-600nm; The temperature of the first heating reaction is 35-40°C and the time is 25-35min; The temperature of the second heating reaction is 85-95°C and the time is 3.5-4.5h.

8. The method according to claim 1, characterized in that: In step 4), the solvent of the dispersion and the mixed solution is ethyl acetate.

9. The method according to claim 1, characterized in that: In step 4), the curing agent includes epoxy resin curing agent and PDMS curing agent.

10. The method according to claim 1, characterized in that: In step 4), The contact angle of the flame-retardant super-hydrophobic self-cleaning coating is greater than 150°, and the rolling angle is less than 10°; The curing temperature is 80-90° C. and the curing time is 2-3 hours.

Citation Information

Patent Citations

  • Ammonium polyphosphate / SiO2 composite aerogel flame-retardant reinforced timber and preparation method thereof

    CN104760103A

  • Wear-resistant and stable flame-retardant super-hydrophobic / super-oleophobic coating as well as preparation and application thereof

    CN114250005A

  • Super-hydrophobic / super-oleophobic flame-retardant heat-insulating coating and preparation method thereof

    CN114479541A

  • Manufacturing method for flame-retardant, hert- resistant lumber

    JP2001252908A

  • A flame retardant coating composition prepared by the sol-gel method and a preparation method thereof

    KR102708866B1